Adding a puzzle piece to the scorpion distribution: expanding the records of Tityus (Tityus) confluens Borelli, 1899 (Scorpiones, Buthidae) in southern Brazil - Margonari Goldoni, Paulo André; Iniesta, Luiz Felipe M.; Marques-da-Silva, Emanuel; Brescovit, Antonio D. (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
New records for the species Tityus (Tityus) confluens Borelli, 1899, previously known from the states of Ceará, Mato Grosso, Mato Grosso do Sul, Piauí, and Tocantins in Brazil, are made for the state of Paraná. In addition, an updated map with these new records from Brazil is provided.
Keywords: Neotropical; Paraná; América do Sul; Escorpiofauna; Buthidae